2019
DOI: 10.1039/c9ra00742c
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthesis of a clay supported amorphous aluminum nanocomposite and its application in removal of hexavalent chromium from aqueous solutions

Abstract: Synthesis and application of bentonite supported amorphous aluminum nanocomposite as promising material for the removal of Cr(vi) from aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…It is worth mentioning that no study was found on surface charge measurements by means of zeta potential for bentonites or montmorillonites from Cubati region. The negative surface charge is in agreement with studied by [58,59], in which bentonites presented high negative charge, although montmorillonite sample studied is less negative. According to [59] the presence of Ca 2+ reduce the magnitude of Zeta potential negative charge, which is in agreement with XRD and XRF results, which presented significant amounts of dolomite and calcium oxide.…”
Section: Resultssupporting
confidence: 89%
“…It is worth mentioning that no study was found on surface charge measurements by means of zeta potential for bentonites or montmorillonites from Cubati region. The negative surface charge is in agreement with studied by [58,59], in which bentonites presented high negative charge, although montmorillonite sample studied is less negative. According to [59] the presence of Ca 2+ reduce the magnitude of Zeta potential negative charge, which is in agreement with XRD and XRF results, which presented significant amounts of dolomite and calcium oxide.…”
Section: Resultssupporting
confidence: 89%
“…SEM microgram sample dosed with a flocculant containing 0.025 and 0.05 M Na 3 PO 4 , and particle size 220 μm during rapid mixing (Figure A2), shows almost identical crystal morphology; that is, large flocs with perforated surface joined together by small flocs. It is suggested that the morphology of the micrographs is attributed to high sorption capacity of the pollutants by permanent negative surface charge and interlayer spaces resulting predominantly in higher ion exchange capacity and metal sorption, an observation already determined by Abbas et al (2018); Chen et al (2018); Delavernhe et al (2015) and Khandelwal et al (2019). Based on the constituents of bentonite clay, saw dust and chemical composition of Na 3 PO 4 , it is conceivable to suggest that optimal removal of the pollutants is dependent upon a large number of pores and abundant surface functional groups (Figure A2), utilized in metal adsorption.…”
Section: Resultsmentioning
confidence: 85%
“…Ionic strength and pH of the solution are a significant factor which influences the adsorbent -adsorbate interaction, by inducing binding site competition and change in the functional group present at the surface of the adsorbent (Khandelwal et al, 2019 ) and a wide range of pH (4-9) on adsorption was studied (Fig. 4).…”
Section: Effect Of Environmental Parameters: Competitive Anions and Phmentioning
confidence: 99%